2012
DOI: 10.1155/2012/907831
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Waste Materials and Organic Amendments on Soil Properties and Vegetative Performance

Abstract: Waste materials, and materials derived from wastes, possess many characteristics that can improve soil fertility and enhance crop performance. These materials can be particularly useful as amendments to severely degraded soils associated with mining activities. This study evaluated biosolids, composts, log yard wastes, and two organic soil treatments for improved soil fertility and vegetative performance using side-by-side comparisons. Each plot was seeded with a standardized seed mix and evaluated for a serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Some waste materials must be capped due to their chemical properties; others can be used for reclamation. Soils can be built by combining waste materials and adding amendments to ameliorate the limiting properties required for vegetation establishment and growth (e.g., [1][2][3]). ese anthroposols, human-made or human-altered soils [4], are important in land reclamation as they use materials that would otherwise need to be handled as waste and may be confined to landfills.…”
Section: Introductionmentioning
confidence: 99%
“…Some waste materials must be capped due to their chemical properties; others can be used for reclamation. Soils can be built by combining waste materials and adding amendments to ameliorate the limiting properties required for vegetation establishment and growth (e.g., [1][2][3]). ese anthroposols, human-made or human-altered soils [4], are important in land reclamation as they use materials that would otherwise need to be handled as waste and may be confined to landfills.…”
Section: Introductionmentioning
confidence: 99%
“…This places a high demand on soils like tropical soils which have a common problem; degradation [1; 6] Increasing crop productivity from these soils has been of paramount importance [7] which has awakened soil researchers on providing information on how to increase soil productivity to meet up with human demands while conserving the soil. Although, chemical fertilizers application had been entertained [8] and found to increase soil productivity however, high cost of chemical fertilizers and subsequent damage to the soil has in time shifted focus of researchers to several forms of organic amendment which are readily available [9]. These organic amendments correct the limitations of chemical fertilizers on soil biophysical properties which include, low structural stability, soil compaction, erosion, low buffering capacity, rapid acidification when cropped continuously with nitrogen fertilizers [10;11].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, soil amendment with oil-cakes of neem, castor, mustard, and other plant products and manures has been successfully used for the control of plant parasitic nematodes, especially Meloidogyne spp. [15]. Many different researchers have reported that Sudangrass and sorghum (Sorghum sudanense), Cruciferae, like oil radish (Raphanus sativus) and rapeseed (Brassica napus), ricin (Ricinus communis), marigold (Tagetes erecta, T. patula, T. minuta) and velvet bean (Mucuna deeringiana) are very effective on RKNs [16,17].…”
Section: Introduction mentioning
confidence: 99%